Operações em serviços de saúde: Um estudo em uma organização de “saúde suplementar” - Dockhorn, Marcelo da Silva Mello (Universidade do Vale do Rio dos Sinos, 2009)
The goal of this research is to identify how the customer experience of a private health care company can be reflected in the organizational management, under the organization point of view. The study presents a qualitative and exploratory approach, using case studies of different health organizations all part of one same national confederation in different regions of the state of the Rio Grande Do Sul. The relations between the theory and the practice followed two main lines: The health services provided by those different units and its relationship with the customer. The private health care companies have as its main product “the health plan” and its function is provide the link between the customer and the health service provider. In this research, were made and studied 16 interviews and observations. The operations had been classified, in accordance with its function for the maintenance of the customer health, in: Protection, Prevention, Care and Rehabilitation, according the health actions proposed by Alma Atta (1978). It was identified de predominance of Prevention and Care services. Regarding the relationship with the customer, the Idea was to identify the way or ways how these organizations relate with their customers. It was observed intention of knowing the customer trough the attention to its observations and by following the customer behavior in the interaction with the organization. The consequence of the customer experience seems to present two distinct outputs. The improvement of the existing services and the creation of new ones.
Keywords: Gestão; Operações; Cliente; Saúde suplementar; Administração de serviços em saúde; Management; Operations; Customer; Private health; Health services management; ACCNPQ::Ciências Sociais Aplicadas::Administração